2019
DOI: 10.1002/humu.23817
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in the erythroid transcription factor KLF1 is likely responsible for ameliorating β‐thalassemia major

Abstract: We describe the identification of a novel missense mutation in the second zinc finger of KLF1 in two siblings who, based on their genotype, are predicted to suffer from beta thalassemia major but are, in fact, transfusion‐free and in good health. These individuals, as well as two additional members of the same family also carrying this KLF1 mutation, exhibit high levels of fetal hemoglobin (HbF). KLF1 is an erythroid transcription factor, which plays a critical role in the regulation of the developmental switc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(52 reference statements)
2
8
0
Order By: Relevance
“…KLF1 mutations can cause borderline high Hb A 2 levels 16–18 . KLF1 has also been reported to ameliorate the severity of beta‐thalassaemia disease 19–21 . The findings were demonstrated in a pair of twins who had beta‐thalassaemia major with discrepant clinical severity.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…KLF1 mutations can cause borderline high Hb A 2 levels 16–18 . KLF1 has also been reported to ameliorate the severity of beta‐thalassaemia disease 19–21 . The findings were demonstrated in a pair of twins who had beta‐thalassaemia major with discrepant clinical severity.…”
Section: Introductionmentioning
confidence: 90%
“…[16][17][18] KLF1 has also been reported to ameliorate the severity of beta-thalassaemia disease. [19][20][21] The findings were demonstrated in a pair of twins who had beta-thalassaemia major with discrepant clinical severity. The twin who harboured a co-inherited KLF1 mutation was non-transfusiondependent.…”
Section: Introductionmentioning
confidence: 91%
“…KLF1 is a zinc-finger DNA binding protein that binds specifically to the 5′-CCMCRCCCN-3′ motif on most erythroid-specific genes. Furthermore, KLF1 acts as a positive regulator of BCL11A transcription factor expression to control the levels of HbF [ 39 ].…”
Section: Factors Involved In the Transcription Control Of The Hbb Locusmentioning
confidence: 99%
“…The latest findings by Fanis et al [ 39 ] revealed a novel missense mutation in the second zinc-finger domain of the KLF1 protein, in two siblings who were predicted to have β –thalassemia major based on their genotype (IVS1-110); however, they were both transfusion-free and healthy. Another two family members also exhibited a high level of HbF while carrying a similar KLF1 mutation.…”
Section: Factors Involved In the Transcription Control Of The Hbb Locusmentioning
confidence: 99%
“…Physical examination was unremarkable, without signs of anaemia, such as jaundice, paleness, splenomegaly and hepatomegaly. To investigate her unexpected mild phenotype, known genetic modifiers that ameliorate the severity of β‐thalassemia were analysed (Fanis et al, 2019 ; Lai et al, 2016 ; Razak et al, 2018 ). A heterozygous KLF1 mutation (c.519_525dup) and two homozygous SNP variants, rs7776054 and rs9399137, in the HBS1L ‐ MYB locus were identified [Figure 1d ].…”
Section: Clinical Presentationmentioning
confidence: 99%